REVIEW OF VISUAL AND CULTURAL LANDSCAPES CONSERVATION IN TOURISM DEVELOPMENT: CASE STUDY OF WAKATOBI REGENCY, SOUTHEAST SULAWESI PROVINCE - Ray March Syahadat (Jurnal Infrastruktur, 2021)
Maybe some people still don't know when they hear the term of visual pollution. However, visual objects are important assets in supporting the character of an area. Even these visual objects sometimes become landmarks or ecomarks in the area and then become a tourist attraction. Unlike other countries, which already have regulations on visual preservation, in Indonesia it seems that no one has spoken out loud about this issue. Without regulations regarding visual preservation, it can pose a threat in the form of a source of visual discomfort that has an impact on the image of the area and tourism. Likewise with the uniqueness of the cultural landscape, both tangible and intangible, the wrong handling will eliminate the values ​​in it. This article aims to provide an overview of the position of tourism policies made by local governments in an effort to preserve the visual and cultural landscape using a case study approach in Wakatobi Regency, Southeast Sulawesi. Wakatobi was chosen because it is one of Indonesia's ten priority destinations which, after receiving special attention from the government, began to show the development of tourism infrastructure. The data sources used in this study were secondary data obtained from various research articles, documents, reports, and related legal products. This article is expected to provide an enrichment of literature related to the preservation of visual and cultural landscapes in tourism. The results show that there is no specific policy to protect visual preservation in Wakatobi. Compared to visual preservation, efforts to preserve the cultural landscape are far more developed, although not yet deep.